2013
DOI: 10.4047/jap.2013.5.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Comparative fracture strength analysis of Lava and Digident CAD/CAM zirconia ceramic crowns

Abstract: PURPOSEAll-ceramic crowns are subject to fracture during function. To minimize this common clinical complication, zirconium oxide has been used as the framework for all-ceramic crowns. The aim of this study was to compare the fracture strengths of two computer-aided design/computer-aided manufacturing (CAD/CAM) zirconia crown systems: Lava and Digident.MATERIALS AND METHODSTwenty Lava CAD/CAM zirconia crowns and twenty Digident CAD/CAM zirconia crowns were fabricated. A metal die was also duplicated from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Therefore, the technique and the low mechanical properties of the veneer material may be the reason for this mode of failure as well as for the lower fracture strength presented by specimens in BL group, since the inner coping was still intact after the mechanical testing. In contrast, there are some researches reporting complete failure (core/veneer) of all Lava CAD/CAM crowns [ 7 ] and total coping fracture [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the technique and the low mechanical properties of the veneer material may be the reason for this mode of failure as well as for the lower fracture strength presented by specimens in BL group, since the inner coping was still intact after the mechanical testing. In contrast, there are some researches reporting complete failure (core/veneer) of all Lava CAD/CAM crowns [ 7 ] and total coping fracture [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation of clinical survival rates of posterior all-ceramic crowns and fixed dental prostheses (FDPs) reveals the vulnerability of those systems to various failure modes [ 4 6 ]. Therefore, several attempts have been made to improve the fracture strength of all-ceramic restorations, including the use of Yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) due to its higher flexural strength [ 7 ] that allows the manufacturing of fixed partial prostheses (FPPs) in areas of high masticatory loads [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The load was applied on each specimen until catastrophic failure occurred. Catastrophic failure was defined as exhibition of visible cracks and events of chipping or fracture [27]. The failure load was recorded in newton on a reading monitor for each sample, and the fractured crowns were examined under the stereomicroscope to determine the fracture mode of each sample which was classified as following [18, 27, 28]: Mode I: visible cracks in the crown. Mode II: veneer chipping. Mode III: bulk fracture of the crown.…”
Section: Methodsmentioning
confidence: 99%
“…On testing and comparing the above materials, it was concluded that the performance of VMII crowns was superior to YZ crowns in the fatigue test, and Lava crowns showed a complete fracture of both the veneering porcelain and the core, whereas the Digident crowns showed fracture only of the veneering porcelain. [15] Kwon et al [15] conducted a study where they compared the fracture strengths of two CAD/CAM zirconia crown systems that is Lava and Digident. Zahran et al [9] in their study compared fracture strength and fatigue resistance of In-Ceram YZ crowns and feldspathic all-ceramic crowns made with CAD/CAM.…”
Section: Discussionmentioning
confidence: 99%